Novel bi-allelic variants of CHMP1A contribute to pontocerebellar hypoplasia type 8: additional clinical and genetic evidence - He, Tiantian; Sun, Huaqin; Xu, Bocheng; Qu, Haibo; Cai, Xiaotang; Zhou, Hui; Liu, Yanyan; Lin, Ziyuan; Zhang, Xuemei (Frontiers in Neurology, 2023)
Pontocerebellar hypoplasia type 8(PCH8) is a rare neurodegenerative disorder, reportedly caused by pathogenic variants of the CHMP1A in autosomal recessive inheritance, and CHMP1A variants have also been implicated in other diseases, and yet none of the prenatal fetal features were reported in PCH8. In this study, we investigated the phenotype and genotype in a human subject with global developmental delay, including clinical data from the prenatal stage through early childhood. Prenatally, the mother had polyhydramnios, and the bilateral ventricles of the fetus were slightly widened. Postnatally, the infant was observed to have severely delayed psychomotor development and was incapable of visual tracking before 2 years old and could not fix on small objects. The young child had hypotonia, increased knee tendon reflex, as well as skeletal malformations, and dental crowding; she also had severe and recurrent pulmonary infections. Magnetic resonance imaging of the brain revealed a severe reduction of the cerebellum (vermis and hemispheres) and a thin corpus callosum. Through whole exome sequencing and whole genomics sequencing, we identified two novel compound heterozygous variations in CHMP1A [c.53 T > C(p.Leu18Pro)(NM_002768.5) and exon 1 deletion region (NC_000016.10:g.89656392_89674382del)]. cDNA analysis showed that the exon1 deletion region led to the impaired expression, and functional verification with zebrafish embryos using base edition indicated variant c.53 T > C (p.Leu18Pro), causing dysplasia of the cerebellum and pons. These results provide further evidence that CHMP1A variants in a recessive inheritance pattern contribute to the clinical characteristics of PCH8 and further expand our knowledge of the phenotype and genotype spectrum of PCH8.